The Metabolic Landscape of Lung Cancer: New Insights in a Disturbed Glucose Metabolism - Vanhove, Karolien; Graulus, Geert-Jan; Mesotten, Liesbet; Thomeer, Michiel; Derveaux, Elien; Noben, Jean-Paul; Guedens, Wanda; Adriaensens, Peter (Frontiers in Oncology, 2019)
Metabolism encompasses the chemical processes that allow healthy cells to keep energy, redox balance and building blocks required for cell development, survival, and proliferation steady. Cancer cells are well documented to rewire their metabolism and energy production networks to support rapid proliferation and survival in harsh conditions via the activation of oncogenes and inactivation of tumor suppressor genes. Despite the histologic and genetic heterogeneity of tumors, a common set of metabolic pathways sustain the high proliferation rates observed in cancer cells. This review with a focus on lung cancer covers several fundamental principles of the disturbed glucose metabolism, such as the ‘Warburg’ effect, the importance of the glycolysis and its branching pathways, and the unanticipated gluconeogenesis. Furthermore, we highlight our current understanding of the disturbed glucose metabolism and how this might result in the development of new treatments.